Avoiding Clinical Trial Failures in Neglected Tropical Diseases: The Example of Chagas Disease. (14th November 2022) - Tarleton, Rick L
Abstract: Human clinical trials are expensive, and when they fail, they create the impression that a problem is intractable, thus depressing interest in future attempts. For neglected tropical diseases, where there are likely limited numbers of "shots on goal, " such failures need to be assiduously avoided. Chagas disease drug discovery efforts have experienced more than its share of human clinical trial failures. Here are some guidelines, many specific for Chagas, but some that might also have application for other neglected tropical diseases. Chagas disease has major challenges (eg, the lack of a definitive test of cure) but also has outstanding advantages, among these the unmatched multi-species natural infection systems that can be exploited to de-risk compounds before human trials. Fully utilizing these advantages while frankly acknowledging and addressing the challenges should bring better options to patients, sooner. Abstract : A string of clinical trial failures in Chagas disease prompts evaluation of the funding and decision-making processes in these human experiments, including the minimal data needed to go forward, the trial format and how pre-trial and trial results are reported.